2005
DOI: 10.1164/rccm.200408-1064oc
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene Modifier Therapy for Mild Sleep-disordered Breathing in Children

Abstract: Background: Children with mild sleep-disordered breathing (SDB), who may not be recommended for adenotonsillectomy, frequently exhibit neurocognitive and behavioral morbidity, and may benefit from alternative therapeutic interventions, such as leukotriene modifier therapy. Methods: Twenty-four children with SDB completed an open-label intervention study for 16 weeks with daily montelukast therapy. Sleep studies and adenoid size estimates from lateral X-ray films of the neck were obtained before and after treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
157
0
11

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 280 publications
(179 citation statements)
references
References 45 publications
7
157
0
11
Order By: Relevance
“…Expression of cysteinyl leukotriene receptors was found increased in tonsillar tissues of children with OSA. [43] In a clinical trial, montelukast was used for 16 weeks in children with sleepdisordered breathing. Adenoid size was found to be decreased and obstructive apnea/hypopnea index, apnea index, respiratory-related arousal index, and sleep pressure scores were improved significantly with montelukast treatment.…”
Section: Adenoidectomy Indicationsmentioning
confidence: 99%
“…Expression of cysteinyl leukotriene receptors was found increased in tonsillar tissues of children with OSA. [43] In a clinical trial, montelukast was used for 16 weeks in children with sleepdisordered breathing. Adenoid size was found to be decreased and obstructive apnea/hypopnea index, apnea index, respiratory-related arousal index, and sleep pressure scores were improved significantly with montelukast treatment.…”
Section: Adenoidectomy Indicationsmentioning
confidence: 99%
“…Oral montelukast has been used in children with mild to moderate OSA. Previous clinical studies, [4][5][6][7] including double-blind and placebo-controlled trials, have shown that treatment with montelukast significantly reduced adenoid size and reduced respiratory-related sleep disturbances in children with mild to moderate OSA. An open study 4 reported that obstructive apnea index was reduced from 3.0 to 2.0 and the A/N ratio was decreased from 0.76 to 0.56 after 16 w of montelukast therapy.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, increased levels of NO, IL-6, and 8-isopentane can be detected in exhaled condensates from the upper airway of adults with OSA (32)(33)(34), and increased numbers of neutrophils, as well as increased concentrations of bradykinin and vasointestinal peptide have been measured in nasal lavage fluid from such patients (35). Furthermore, adenotonsillar tissues of children with OSA display increased expression levels of leukotriene receptors along with increased concentrations of leukotrienes (36,37). Mechanoreceptors and sensory nerves are crucial for tonic and dynamic maintenance of upper airway patency (38), such that the abnormal varicose nerves that are found in the soft palate tissues of OSA patients suggest that alterations in innervation of the upper airway may lead to changes in upper airway protective function (39).…”
Section: Discussionmentioning
confidence: 99%